Atomic insights into interface-mediated plasticity and engineering principles for heterogeneous serrated interfaces. (January 2023) - Zhang, Y.; Liu, Z.R.; Yao, B.N.; Legut, D.; Zhang, R.F.
Highlights: Representative Cu/Nb interfaces show novel interface-mediated deformation behaviors. Stress inhomogeneity due to serration mismatch affects the deformation twinning. The symmetry of highly distorted atomic hexagons shapes the dislocation nucleation. Serrated and planar interfaces show different deformation behaviors. Three screened critical descriptors are proposed for engineering interfaces. Abstract: Metallic nanolayered composites typically experience substantially enhanced resistance to irreversible deformation as the portion of interfaces increases. Three-dimensional (3D) serrated interfaces possess considerably higher resistance to interface-facilitated plasticity than two-dimensional (2D) planar interfaces; however, the atomistic mechanisms underlying this phenomenon are little explored, while the engineering principles of tailoring atomic serrations are nearly unknown. In this study, two known representative serrated interfaces, i.e., Cu{991}//{112}Nb and Cu{112}//{112}Nb interfaces, are analyzed using atomic-scale simulations and interfacial dislocation theory and comprehensively compared with their planar counterparts. The Cu{991}//{112}Nb and Cu{112}//{112}Nb serrated interfaces exhibit the novel interface-facilitated deformation behaviors of deformation twinning and near-interface dislocation nucleation, respectively. The stress inhomogeneity arising from the geometrical mismatch between Cu and Nb serrations contributes to deformation twinning rather than dislocation nucleation, while the improved symmetry of highly distorted atomic hexagons on the extended Cu{111}//{110}Nb facets dominates the near-interface dislocation nucleation. Both deformation twinning and dislocation nucleation are closely related to the geometry and characteristics of atomic serrations at the interfaces, which differ from those observed in planar interfaces. Further systematic investigations of fourteen serrated interfaces derived from Cu{991}//{112}Nb and Cu{112}//{112}Nb suggest that the screened facet planes, free volume, and Poisson's ratio mismatch may be used as critical descriptors to tailor the mechanical properties and responses, which presents a convenient solution for interface engineering. These findings provide not only novel atomistic mechanisms that explain the localized interface-facilitated plasticity, but also general principles for engineering atomically serrated interfaces. Graphical abstract: Image, graphical abstract